To govern is to serve: an essay on medieval democracy - Dalarun, Jacques (Medieval Societies, Religions, and Cultures, 2023)
To Govern Is to Serve -- Contents -- Series Editors' Foreword -- List of Abbreviations -- Translator's Introduction -- Preface -- Part One: The Servant Served -- 1. A Shocking Story -- 2. Sisters -- 3. Assisi -- 4. Ritual -- 5. Body -- 6. Inversions -- 7. Paradox -- Part Two: Unworthiness in Power -- 1. Benedictine Beginnings -- 2. Fontevraud -- 3. The Paraclete -- 4. Grandmont I: Facts -- 5. Grandmont II: Conjectures -- 6. Preachers -- 7. Lesser Brothers I: Writings by and about Francis -- 8. Lesser Brothers II: Chronicles -- 9. Lesser Brothers III: About Face -- 10. Experiments -- Part Three: Maternal Government -- 1. Treasure Trove -- 2. Pastorate -- 3. A Note -- 4. Mother -- 5. Word by Word -- 6. Resumption -- 7. Bonds -- Afterword -- Bibliography -- Index.